Analisis Yuridis Tentang Tindakan Indonesia Membatasi Impor Produk Baja Bukan Paduan Dari Taiwan dan Vietnam Berdasarkan Prinsip Safeguard: Juridical Analysis of Indonesia Restricting Non-Alloy Steel Imports from China, Taipei, and Vietnam According to Safeguard Principle - Maharani, Dhaniswara; Sukarmi; Rachmawati, Yasniar (Brawijaya Law Student Journal, 2023)
Abstract This research investigates whether the measures taken by Indonesia to implement the security of steel imports from Taiwan and Vietnam comply with the provisions of international economic law—Safeguard on Certain Iron or Steel Products (DS496). This dispute began when Indonesia put security in place against Galvalume. The Regulation of Finance Minister of the Republic of Indonesia Number 137.1/PMK.001/2014 put in place on 22 July 2014 in 2015 implies that Taiwan and Vietnam raised a claim against Indonesia according to Articles 1 and 4 concerning Understanding on Rules and Procedures Governing the Settlement of Disputes (DSU), Article XXII of GATT 1994 and Article 14 of Safeguards Agreement concerning policies in Indonesia regarding Galvalume. This research employed normative-juridical methods supported by case and statutory approaches, revealing that Indonesia is deemed to have violated the regulatory provisions of WTO and was declared guilty. In this case, Vietnam requested retaliation from an Arbitral Board of WTO demanding that Indonesia pay the compensation for the losses caused in galvalume trade from Vietnam. Indonesia and Vietnam agreed to settle the dispute through a bilateral agreement following the recommendation from the panels of WTO. Keywords: Galvalume, Safeguard Measures, Settlement of International Economic Disputes Abstrak Penelitian ini membahas tentang apakah upaya Indonesia menerapkan tindak pengamanan impor produk baja dari Taiwan dan Vietnam sudah sesuai dengan ketentuan hukum ekonomi internasional terkait Indonesia – Safeguard on Certain Iron or Steel Product (DS496).Sengketa ini bermula ketika Indonesia melakukan tindakan pengamanan terhadap impor Baja Alumunium Lapis Seng (atau sering dikenal dengan galvalum) yang berdasarkan dengan Peraturan Menteri Keuangan Republik Indonesia nomor 137.1/PMK.011/2014 yang diberlakukan pada 22 Juli 2014 Pada 2015, Taiwan dan Vietnam mengajukan tuntutan kepada Indonesia berdasarkan Pasal 1 dan 4 Understanding on Rules and Procedures Governing the Settlement of Disputes (DSU), pasal XXII dari GATT 1994, serta pasal 14 dari Perjanjian tentang Safeguards, mengenai kebijakan yang diambil Indonesia terhadap impor BjLAS. Jenis penelitian adalah yuridis-normatif dengan menggunakan pendekatan kasus dan peraturan perundang-undangan. Indonesia dianggap melangar aturan-aturan yang sudah dibuat dalam ketentuan perdagangan WTO dan dinyatakan bersalah, sehingga Vietnam mengajukan retaliasi pada badan arbitrase WTO agar Indonesia membayar kerugian perdagangan glavalum dari Vietnam. Pada akhirnya Vietnam-Indonesia sepakat menyelesaikan kasus sengketa dagang tersebut melalui perjanjian bilateral atas rekomendasi dari panel WTO. Kata Kunci: Galvalum, Penyelesaian Sengketa Ekonomi Internasional, Tindakan Pengamanan